Biomechanical Alteration of Stress and Strain Distribution Associated with Vertebral Fracture / Muhammad Hazli Mazlan...[et al.] - Mazlan, Muhammad Hazli; Mitsugu, Todo; Ikuho, Yonezawa; Hiromitsu, Takano (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The phenomenon of recurrent fractures at the adjacent level of a fractured vertebra is becoming a major concern amongst medical practitioners. To date, the underlying cause of this phenomenon is still elusive; therefore, a further investigation is in dire need in order to achieve satisfactory clinical outcomes in the future. In the present study, an image based finite element analysis (FEA) was used to investigate the biomechanical alterations of spine that have been diagnosed with first lumbar (L1) vertebral compression fracture as compared to a healthy spine. The FEA assessment was made based on the model's stress and strain distributions. A complimentary examination of bone density distribution and kyphotic deformity angle of the model would give further details on the underlying cause of this phenomenon. The results showed that the vertebral fracture model tends to produce higher stresses and strains generation in comparison to the healthy vertebral model, especially at the adjacent level of the fractured vertebra. These conditions were highly correlated to the bad quality of the bone strength due to osteoporosis, and the kyphotic structural of the fractured vertebral model. The combination of these two elements has put the structural integrity of the vertebrae at the stake of bone fracturing even under the influence of daily living activity.